Efficiency of degradation or desorption methods in antineoplastic drug decontamination: A critical review. (June 2019) - Simon, Nicolas; Odou, Pascal; Decaudin, Bertrand; Bonnabry, Pascal; Fleury-Souverain, Sandrine
Although considerable efforts have been made over the last 40 years, occupational exposure to antineoplastic drugs is still a daily concern, since eradicating such contamination from workplaces seems unattainable. Considerable data are currently available on the risks associated with their use at work. Hospital facilities are often cleaned with marketed antimicrobials whose chemical decontamination efficacy certainly differs but remains unknown. To keep compounding facilities sterile, alcohol-based solutions are frequently used but with very limited efficiency. It would be particularly useful if a decontamination method could be added to the means already available so that all conventional antineoplastic drug contamination could be removed. Several degradation methods or desorption methods have previously been experimented, with varying success. They have never been compared or discussed in terms either of efficiency or usability. This review aims to analyse and discuss the results of each degradation or decontamination procedure and to compare them. This should facilitate selection of the method to be implemented in daily practice.